Adaptive potential of spring durum wheat (Triticum durum Desf.) under the conditions of Primorsky Territory - P. M. Bogdan; A. G. Klykov; I. V. Konovalova; N. V. Kuzmenko (Труды по прикладной ботанике, генетике и селекции)
Background. The research goal was to study spring durum wheat cultivars from different regions of Russia to select those that were most adapted to the conditions of Primorsky Territory and had high yield and grain quality.Materials and methods. The adaptive potential of 16 genotypes was determined through multi-environment trials at the Federal Scientific Center of Agricultural Biotechnology of the Far East named after A.K. Chaika in 2017–2021.Results. Considerable potential for high productivity was revealed in the cultivars: ‘Solnechnaya 573’ (3.9 t/ha), ‘Donskaya elegiya’ (3.8 t/ha), ‘Lyudmila’ (3.8 t/ha), ‘Omskii izumrud’ (3.8 t/ha), and ‘Voronezhskaya 7’ (3.8 t/ha). Cvs. ‘Pamyati Yanchenko’ (–2.1), ‘Zhemchuzhina Sibiri’ (–2.4), and ‘Voronezhskaya 7’ (–2.4) displayed significant stress resistance. ‘Lyudmila’ (4.2) and ‘Donskaya elegiya’ (4.0) had high genetic plasticity and produced high yields in the years with favorable conditions. The adaptability coefficient of cvs. ‘Solnechnaya 573’ (112.5%) and ‘Voronezhskaya 7’ (111.0%) exceeded 100%. ‘Donskaya elegiya’, ‘Lyudmila’, ‘Aleiskaya’, and ‘Voronezhskaya 9’ demonstrated the highest plasticity (bi > 1). The most stable cultivars were ‘Omskii tsirkon’ (S2di – 0.00), ‘Pamyati Yanchenko’ (S2di – 0.02), ‘Voronezhskaya 7’ (S2di – 0.04), ‘Aleiskaya’ (S2di – 0.05), ‘Nikolasha’ (S2di – 0.06), and ‘Omskaya biryuza’ (S2di – 0.08). ‘Voronezhskaya 7’ and ‘Pamyati Yanchenko’ were able to produce an increased yield and had the minimum yield loss under unfavorable conditions (the indicator of the yield stability of the cultivars was 134.9 and 144.8, respectively). ‘Pamyati Yanchenko’ (4.8 and 1.9, respectively) and ‘Voronezhskaya 7’ (3.5 and 2.0, respectively) showed high homeostatic capacity and breeding value.Conclusions. ‘Voronezhskaya 7’ and ‘Solnechnaya 573’ were selected on the basis of complex evaluation for yield and adaptability under the local conditions. They can be recommended for further breeding and production.